(untitled) (Proceedings of the International Conference on Social Sciences, 2023)
The study establishes whether public equity finance leads to the growth of an SME. SMEs often lack the capital required for growth. The Johannesburg Stock Exchange established AltX specifically for SMEs to participate in equity markets, enabling them to raise growth capital. However, some firms that listed on the AltX migrated to the Mainboard while some delisted, suggesting that listing may have a positive or a negative impact on the growth of an SME. To understand various sources of finance and how these impact on the growth of firms, the Pecking Order Theory of Capital Structure was adopted as a framework. Total population sampling was used where 81 currently and migrated AltX listed firms were approached for interviews. Data was collected through in-depth interviews from the eleven firms that responded. These firms span a range of different sectors, with an average annual turnover of R200-R500 million. Data was qualitatively analysed with ATLASti and then empirically using fuzzy set Qualitative Comparative Analysis (fsQCA), to determine the relationship between listing and growth. The study found that public equity led to the growth of SMEs. However, there are tangible and intangible attributes of listing that result in the growth of a firm, namely, raising capital (public equity) and credibility. The credibility associated with being listed led to the growth of more SMEs, than raising capital. The study recommends a significant increase in the marketing efforts of the AltX to attract more SMEs to list and better support structures to assist with the growth of listed SMEs. There are limited studies on this form of SME financing and this study contributes to the pool of literature on the subject.